Saberes da pesca artesanal e a proposição do currículo para as escolas do campo em Bragança, Estado do Pará, Brasil - SOUSA, Antônia Andresa dos Santos (2023)
The present work aims to understand the knowledge of artisanal fishing in the community of Tamatateua as a curriculum proposition for field schools, in Bragança, State of Pará. The theoretical references that guide the analysis are: Caldart (2004); Castro (1999); Hage (2016); Diegues (2001); Geertz (1989); Moraes (2007), among others. Methodologically, the research is based on a qualitative approach and uses documental and field research in data collection. The results achieved indicate that the study of cultural identity in the fishing perspective in Bragança-PA emerged from the production of guiding knowledge for field schools, they are: the life history of fishermen; fishing work and gender relations; fishing time: construction of an annual fishing calendar; types of fish, river, and fishing (industrial and artisanal), species reproduction time; fishing techniques and their seasons with nature; (public policies) legislation: legal frameworks that limit artisanal fishing (rights and duties); fishing and its form of family economy and commercialization of fish; artisanal fishing artifacts; fisheries and sustainable development in the community; environmental and social impacts; generational knowledge and the (Dis)valuation of artisanal fishing. In view of this, this knowledge has a dynamic in time and space inserted by the differences between the types of fishing: artisanal and industrial, in which there is the devaluation of artisanal fishing, in addition, the community has environmental impacts, which influence the disappearance of the local ichthyofauna